2015
DOI: 10.1530/erc-14-0302
|View full text |Cite
|
Sign up to set email alerts
|

RhoB upregulation leads to either apoptosis or cytostasis through differential target selection

Abstract: Anaplastic thyroid carcinoma is a highly aggressive undifferentiated carcinoma with a mortality rate near 100% that is due to an assortment of genomic abnormalities that impedes the success of therapeutic options. Our laboratory has previously identified that RhoB upregulation serves as a novel molecular therapeutic target and agents upregulating RhoB combined with paclitaxel lead to antitumor synergy. Knowing that histone deacetylase (HDAC) 1 transcriptionally suppresses RhoB, we sought to extend our findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…The three GADD45 (growth arrest and DNA damage inducible 45) protein family members induce apoptosis by binding and activating MAP3K4 kinase, which in turn positively regulates the p38/JNK-mediated apoptotic pathway [21,24]. RHOB (ras homologue family member B), in turn, activates apoptosis by positive regulation of JNK that triggers the activation of pro-apoptotic BCL2L11 [25,26]. We propose that abrogated inhibition of the above-mentioned four pro-apoptotic mRNAs upon expression of mutated NANOS1 accounts for increased apoptosis of TCam-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…The three GADD45 (growth arrest and DNA damage inducible 45) protein family members induce apoptosis by binding and activating MAP3K4 kinase, which in turn positively regulates the p38/JNK-mediated apoptotic pathway [21,24]. RHOB (ras homologue family member B), in turn, activates apoptosis by positive regulation of JNK that triggers the activation of pro-apoptotic BCL2L11 [25,26]. We propose that abrogated inhibition of the above-mentioned four pro-apoptotic mRNAs upon expression of mutated NANOS1 accounts for increased apoptosis of TCam-2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, RhoB expression is predictive of an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) response; a EGFR-TKI/Akt inhibitor combination provides a clinical advantage in preventing resistance to EGFR-TKI for RhoB-positive tumor patients ( 26 ). A number of studies have identified a loss of RhoB expression in head, neck, gastric, renal and lung cancer ( 29 – 31 ). Studies of RhoB gene knockout in mice demonstrated that the frequency of chemically induced neoplastic transformation increased, and that the overexpression of RhoB in human cell lines results in the inhibition of signal transduction pathways associated with oncogenesis and tumor survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, each of the three GADD45 (growth arrest and DNA damage inducible) protein family members induces apoptosis by binding and activating MAP3K4 kinase, which in turn positively regulates p38/JNK cascade [24]. RHOB (ras homolog family member B), on the other hand, activates apoptosis via BCL2L11 BIM activation [25]. Given our obtained results, we propose that lack of repression of above mentioned four pro-apoptotic mRNAs upon expression of p.[(Pro34Thr);(Ser83del)] NANOS1 mutation accounts for increased apoptosis of TCam-2 cells.…”
Section: Discussionmentioning
confidence: 99%